BIMTEK PENGENALAN PENYAKIT BUSA BATANG/DIPLODIA JERUK SIOMPU DAN PENGENDALIAN MENGGUNAKAN PHYMAR C 67SL - Terry Pakki; Husna; Abdul Munif; Prayogo Probo Asmoro; Asniah; Irdika Mansur; Hamirul Hadini; Faisal Danu Tuheteru; Alba; Mazhfia Umar; Wa Ode Yusria; La Ode Kasno Arif; La Ode M Erif; Herlan Hidayat; Jusman Saribadu; Dahlan (Jurnal Pengabdian Pada Masyarakat MEMBANGUN NEGERI, 2023)
Siompu Island in South of Buton has potential for superior horticultural crops. The plant is Siompu citrus. Siompu citrus are famous for having the number one sweet taste in Indonesia. Fruit productivity in the last decade has continued to decline. One of the causative factors is pest and disease attacks. Stem foam/diplodia disease caused by Botryodiplodia theobromae is common in Siompu citrus plantations on Siompu Island. Introduction and control of stem foam to citrus farmers needs to be done. The aim of technical guidance is to strengthen the capacity of knowledge and skills of farmers. Technical guidance on the introduction of Siompu citrus stem foam disease and its control using PHYMAR C 67SL was carried out on March 8-11 2023 at the Siompu of state Senior High School 1 Hall and several Siompu Citrus farmer gardens in Siompu District, South Buton Regency with 35 participants. The method that will be used in this program is the Technology Transfer method. The results of the service showed that there was an increase in the knowledge and capacity of farmers regarding the introduction and control of stem foam after the participants attended technical guidance. In addition, after the symptoms of foam attack, the stems were peeled and smeared with Phymar C 67SL which showed dryness.